Immersive Oceans - Leveraging Virtual and Augmented Reality to Advance Ocean Literacy - Angelino, F. J. (Immersive shipwrecks, 2026)
This work explores the integration of immersive technologies, such as virtual reality (VR), augmented reality (AR), mixed reality (MR), and artificial intelligence (AI), to enhance ocean literacy education across all levels of schooling. By leveraging these innovative tools, educators can create engaging, experiential learning environments that foster critical thinking, collaboration, and a deeper understanding of marine ecosystems. The insights gathered highlight the importance of accessibility, curriculum integration, and user-friendly design, while emphasizing the need for teacher training and community engagement. This approach not only motivates students but also equips them with the knowledge and skills necessary to address pressing ocean-related challenges. This work advocates for ongoing research and evaluation to continuously improve the effectiveness of immersive technologies in promoting ocean literacy.